2022
DOI: 10.1371/journal.pone.0272549
|View full text |Cite
|
Sign up to set email alerts
|

Active ageing profiles among older adults in Spain: A Multivariate analysis based on SHARE study

Abstract: Background Following the active ageing model based on the Health, Lifelong Learning, Participation and Security pillars, this research has a twofold objective: i) to classify older adults according to active ageing profiles, taking into account the four pillars, and ii) to ascertain the relationship between the profiles and personal and contextual factors, as well as well-being and quality of life in old age. Methods A study sample of 5,566 Spanish older adults who participated in wave 6 of the Survey of Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 117 publications
(181 reference statements)
1
4
0
Order By: Relevance
“…As in previous studies [ 21 24 ], male sex, younger age, being married, and having a higher level of education were associated with higher odds for active ageing; in our study, these factors characterised those with higher BAEL scores. Compared with women, older men tend to be more engaged in socially oriented activities outside the home [ 25 ], which has been suggested to be one factor underlying better subjective well-being [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As in previous studies [ 21 24 ], male sex, younger age, being married, and having a higher level of education were associated with higher odds for active ageing; in our study, these factors characterised those with higher BAEL scores. Compared with women, older men tend to be more engaged in socially oriented activities outside the home [ 25 ], which has been suggested to be one factor underlying better subjective well-being [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, when older people’s personal views on how to age successfully were queried, the majority valued engagement in activities and satisfying relationships over health issues [ 28 ]. It is obvious that ageing is not a static state, but instead a dynamic process reflecting an individual’s previous way of life and socioeconomic circumstances in earlier life-course [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…From all existing attempts to measure the aging process, three of them used the SHARE survey ( 10 , 19 , 20 ). We have utilized similar approach as in a study by Sanchez-Niubo et al ( 10 ), where they also based their theoretical framework on the WHO concept of healthy aging.…”
Section: Discussionmentioning
confidence: 99%
“…Rojo-Perez et al [37] identified five distinct profiles of active ageing in older adults in Spain. These profiles range from moderate activity with low physical but moderate social and political engagement to profiles characterized by high participation in cognitive and educational activities.…”
Section: Related Workmentioning
confidence: 99%